Hydraulic properties of unsaturated soils with multi-modal porosity - Wongsodihardjo, Nicholas Stefanus (Nanyang Technological University, 2021)
Hydraulic properties of unsaturated soil - soil-water characteristic curve (SWCC) and unsaturated permeability function - are paramount in understanding changes in water content, pore-water pressures (PWP) and matric suction of unsaturated soil during wetting and drying. Hydraulic properties of soils are largely influenced by porosity and pore size distribution (PSD) of the soil. While there has been a considerable amount of research on bimodal soils, there was hardly any research on multi-modal or trimodal soils. Thus, this project was aimed to study hydraulic properties of unsaturated soil with multi-modal porosity. Three compacted soil specimens: sand-kaolin (SK), sand-kaolin-mica (SKM) and sand-kaolin-activated carbon (SKAC) were studied. Laboratory experiments comprising of dynamic compaction, index property tests, drying and wetting SWCC, shrinkage tests and saturated permeability tests were conducted. In addition, the soil specimens were sent for mercury intrusion porosimetry (MIP) testing to obtain the PSD and pore-size density curve (PDC). Seepage analyses were also conducted to illustrate the performance of the soils during prolonged drying. The experimental result showed that SK and SKM exhibited bimodal drying SWCC, while SKAC exhibited trimodal drying SWCC. A new equation to best fit SWCC with trimodal characteristics was proposed based on Satyanaga et al.’s best-fitting equation for bimodal SWCC. All three soil specimens exhibited unimodal wetting SWCC. Furthermore, SK exhibited the highest permeability function at all suction values compared to SKM and SKAC. The seepage analysis results during an evaporation condition of 7mm/day for 4 days showed that SKM performed better between matric suction of 1-20kPa compared to SK and SKAC, while SKAC was expected to perform better than SKM beyond matric suction of 20kPa as SKAC has a lower permeability than SKM in this suction range.